The Effect of Value Clarification Techniques-Based Civic Education Model on Critical Thinking and Social Attitudes of Fifth Grade Elementary Students - Nirmayani, L. Heny; Yudiana, I Kadek Edi (Universitas Pendidikan Ganesha, 2025)
The critical thinking and social attitudes of elementary school students in Civic Education (CE) learning remain relatively low, indicating the need for an instructional approach that can simultaneously enhance both aspects. This study aimed to analyze the effect of the Value Clarification Techniques (VCT)-based Civic Education learning model on critical thinking skills and social attitudes of fifth-grade elementary school students. The research used a quasi-experimental method with a non-equivalent posttest-only control group design. The sample consisted of 61 students from two elementary schools in Buleleng Regency, selected using cluster random sampling of the intact group type, with 31 students in the experimental group and 30 in the control group. The instruments included a critical thinking test and a social attitude questionnaire. Data were analyzed using descriptive statistics, assumption testing, and MANOVA. The results showed a significant effect of the VCT model on critical thinking (F = 15.72; p < 0.001) and social attitude (F = 11.64; p = 0.001). The experimental group's mean critical thinking score was 81.45, compared to 72.30 for the control group. Similarly, the mean social attitude score of the experimental group was 84.10, higher than the control group's 76.80. These findings indicate that the VCT model is effective in simultaneously fostering students' cognitive and affective development in Civic Education learning.